Prediction of the elastic modulus of LLDPE/CNT nanocomposites by analytical modeling and finite element analysis. (September 2020) - Charitos, Ilias; Drougkas, Anastasios; Kontou, Evagelia
Graphical abstract: Abstract: In the present work, the effective elastic modulus of carbon nanotube (CNT) polymer nanocomposites has been evaluated through micromechanics modeling and finite element analysis (FEA). In the micromechanics model, the inherent trend of CNTs to aggregate is taken into account, considering a two-phase material system, that of the matrix with the finely dispersed CNTs and the inclusions, involving agglomerated CNTs and matrix material. A new model is proposed for the elastic stiffness evaluation of the two phases and the elastic stiffness of the nanocomposite, introducing two aggregation parameters. It was proved that this analysis was rational and operative. The same aggregation concept has been investigated using FEA, and a comparative study between the two procedures was performed. Furthermore, an additional treatment with FEA was performed, based on a three-phase model, including the matrix, the CNTs and the interphase. A parametric analysis has been executed and a comparison with experimental data of linear low density polyethylene (LLDPE)/CNT nanocomposites has been performed.